2017
DOI: 10.2196/jmir.6747
|View full text |Cite
|
Sign up to set email alerts
|

Web-Based Medical Appointment Systems: A Systematic Review

Abstract: BackgroundHealth care is changing with a new emphasis on patient-centeredness. Fundamental to this transformation is the increasing recognition of patients' role in health care delivery and design. Medical appointment scheduling, as the starting point of most non-urgent health care services, is undergoing major developments to support active involvement of patients. By using the Internet as a medium, patients are given more freedom in decision making about their preferences for the appointments and have improv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
121
0
12

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 135 publications
(138 citation statements)
references
References 25 publications
5
121
0
12
Order By: Relevance
“…However, previous research has demonstrated improved reliability, quality and tracking of communication with the introduction of online referral systems . Online appointment scheduling has also been associated with decreased FTA rates in other studies . Our findings are therefore consistent with existing literature and expand on this by providing a paediatric‐specific study.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…However, previous research has demonstrated improved reliability, quality and tracking of communication with the introduction of online referral systems . Online appointment scheduling has also been associated with decreased FTA rates in other studies . Our findings are therefore consistent with existing literature and expand on this by providing a paediatric‐specific study.…”
Section: Discussionsupporting
confidence: 90%
“…Public outpatient clinic patient attendance may be poor, resulting in costly inefficiencies and delays to care. In medical clinics spanning primary care and specialist services, the growing adoption of web‐based medical referral and appointment systems has been associated with an improvement in patient satisfaction and attendance . However, these eHealth initiatives may not attract widespread use and acceptance, and their benefit in paediatric health care in particular is unproven.…”
mentioning
confidence: 99%
“…Improving outpatient attendances to the diversity of pre-existing operational processes and use of IT systems across the different services at GSTT. 9 At the end of the 6-month onboarding phase the DNA rates across the trust dropped from 11.7% to 10.4% (11.1% reduction). Table 2 shows the rates as calculated for the 2016/2017 financial year with numbers in the FBC as the baseline.…”
Section: Landing Pagementioning
confidence: 99%
“…An imperfect proxy indicator is the share of people who make medical appointments online. Web-based medical appointment systems have a number of positive impacts, including improving patient satisfaction, reducing no-shows and wait times (Zhao et al, 2017). Data on the share of individuals who make medical appointments online is available for some European countries (Figure 2.22).…”
Section: Box 23 Ehealth: Technological Advances In Health Carementioning
confidence: 99%